Rancang bangun alat two phase flow (air-udara) sebagai media pembelajaran dan praktikum mahasiswa skala laboratorium - Gunarto, Gunarto; Waspodo, Waspodo; Irawan, Doddy; Julianto, Eko (TURBO [Tulisan Riset Berbasis Online], 2020)
The purpose of this research is to produce a two-phase flow tool as a learning media and practicum based on the engineering approach (BPRT) to increase student motivation, abilities, skills, and understanding of two-phase flow courses. The research stages were carried out by designing the design and manufacturing or assembling of two-phase flow toolswith horizontal and vertical orientations into a complete unit, as well as testing the tools so that they can be used for practicum. Data collection and retrieval were adjusted to the test instruments. The results of this research is a learning media tool and practicum to test the characteristics, determine or look for a pressure drop, and a two-phase flow pattern. This two-phase flow device can operate in horizontal and vertical pipe test sections with minimum water and air flow rate of 0.00017 m3/s or 600 liters/hour while a maximum of 0.0005 m3/s or 1800 liters/hour. The minimum pressure allowed on this tool is 0.3 bar and the maximum is 0.83 bar.Keywords: two phase flow, pressure drop, flow pattern, practicum